A technology for recycling lithium-ion batteries promoting the circular economy: The RecycLib - Santos, M.P. dos [UNESP]; Garde, Ivan Aritz Aldaya [UNESP]; Ronchini, Carolina Magda Bassoto [UNESP]; Filho, Lúcio Cardozo [UNESP]; Souza, Guilherme Botelho Meireles de [UNESP]; Abbade, Marcelo Luís Francisco [UNESP]; Regone, Natal Nerímio [UNESP]; Jegatheesan, Veeriah (Jega) [UNESP]; Oliveira, José Augusto de [UNESP] (Elsevier, 2021)
The demand for lithium-ion batteries (LIBs) is exponentially rising driven by the increasing variety of their applications, which includes consumer electronics, stationary energy storage, and especially electromobility. To meet this increasing demand, recycling becomes necessary since, in addition to reducing the environmental impact of the LIBs, it mitigates the challenges of scarcity of lithium (Li) and other valuable metals such as cobalt (Co), nickel (Ni), and manganese (Mn). In this paper, we propose and demonstrate a technology for recycling LIB cells that recovers active materials and other elements contained in LIB cells. The reported technology, which we denominated RecycLib, employs hydrometallurgy and can be applied to lithium cobalt oxide LiCoO2 (LCO) with cylindrical and prismatic geometries, as well as lithium nickel manganese cobalt oxide LiNixCoyMnzO2 (NMC) cells. Experimental characterization reveals recovery efficiency rates of the cathodic metallic oxide higher than 90 % for LCO (with 98 % purity in the case of cylindrical LIB cells and 80 % for prismatic cells) and 80 % for NMC LIB cells (with 85 % purity) employing relatively inexpensive reagents with low environmental hazardous potential and sub-processes designed according to Circular Economy precepts. Therefore, it is envisaged that the proposed technology to show a low potential for environmental impact, low operating costs, and high work safety, thus favoring industrial scalability.
Keywords: Circular economy; Lithium-ion battery; Recycling